BIOMEDICAL RAPID PROTOTYPING OF FREE-FORM SURFACES BY PLANAR CONTOURS METHOD - Ameddah, Hacene; Mazouz, Hammoudi (6th International Conference Integrity-Reliability-Failure , 22-26 July, 2018)
In this paper, an interactive application tool has been developed for creating 3D models of dental implants and other body structures from 2D medical imaging data. 3D models are generated by using reverse engineering algorithm and planar contour method by SolidWorks developed in Visual Basic Language. The research includes transferring Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) images into digital matrixes, entering digital matrixes into SolidWorks environment, building feature library for 3D reconstruction, creating medical rapid prototyping models, and performing biomedical rapid design and manufacturing. 3D reconstruction models is created by edge configuration, generation and triangulated cube configuration generation in capturing section contour points from medical image per slice, creating B-spline curve with the control points in each layer, producing solid model construction in planar contours method. Medical rapid prototyping models are performed in SolidWorks, including three views or any combination of views, for biomedical rapid designing and manufacturing according to the biomedical needs. Layered manufacturing techniques are used for producing parts of arbitrary complexity. The results of this paper are to develop image processing 3D visualization in SolidWorks Application Programming Interface (API) using Visual Basic Language. The system performance is tested using truth CT and or MRI data, and 3D physical models dental for MRP are created directly from SolidWorks. The results reveal that the accuracy of 3D reconstruction is acceptable.